Welcoming with risk classification in urgent and emergency services: applicability in nursing - Juliana Marques Weykamp; Caroline Silveira Pickersgill; Diana Cecagno; Flavio Peraça Vieira; Hedi Crecencia Heckler de Siqueira (Rev Rene)
Objective: to identify the knowledge of nurses about the implementation the proposal of Welcoming with Risk Classificationin an urgent and emergency service. Methods: this is a study with qualitative approach of descriptive and exploratory type.Data collection was conducted through semi-structured interviews, with the participation of seven nurses who work inthe unit mentioned. Data analysis followed the steps of thematic analysis. Results: they focus on the understanding of participants about welcoming and the facilities and/or difficulties encountered by them due to the implementation of this proposal. Conclusion: it was possible to understand the reality experienced by respondents about the theme and notice thatin spite of the difficulties, they consider that the proposal contributes to the reorganization of the users’ flow and to meettheir demands.